2017
DOI: 10.1155/2017/2539034
|View full text |Cite
|
Sign up to set email alerts
|

A New Unified Intrusion Anomaly Detection in Identifying Unseen Web Attacks

Abstract: The global usage of more sophisticated web-based application systems is obviously growing very rapidly. Major usage includes the storing and transporting of sensitive data over the Internet. The growth has consequently opened up a serious need for more secured network and application security protection devices. Security experts normally equip their databases with a large number of signatures to help in the detection of known web-based threats. In reality, it is almost impossible to keep updating the database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The classification is mainly based on the detection mechanism of the methods.  Signature-based methods [3,4]: this is a well-known approach and has been investigated by many researchers. So far, the research community of web attack detection has built up a complete Core Rule Set [9] to support network users.…”
Section: Related Work 21 Web Attack Detection Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The classification is mainly based on the detection mechanism of the methods.  Signature-based methods [3,4]: this is a well-known approach and has been investigated by many researchers. So far, the research community of web attack detection has built up a complete Core Rule Set [9] to support network users.…”
Section: Related Work 21 Web Attack Detection Researchmentioning
confidence: 99%
“…In this research, he uses an encoding method which reconstructs a character into a 2-dimensional matrix. The authors of the research [14] use N-gram and Generic Feature Selection algorithms to extract features from DARPA and ECML/PKDD2007 datasets [4]. In order to detect abnormal requests, they applied some clustering algorithms like C4.5, CART, Random forest or random tree.…”
Section: Related Work 21 Web Attack Detection Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrete data can be numeric but it can also be categorical, continuous data are always numeric and are not restricted to define separate values and can take any value within a range [31]. The various types of attack with their categories are discussed in the table [32]. The severity of the attack and the classification is discussed.…”
Section: Portsweepmentioning
confidence: 99%
“…Most works of literature have shown that anomaly detection has already been performed using learning techniques either supervised or unsupervised, statistical methods, stream analytic engine and data-mining approaches [6]. Little has been done with regards to reactive protocols used in ad hoc network and key performance indicators to detect outliers in a network.…”
Section: Related Workmentioning
confidence: 99%